Behaviors and influencing factors of Chinese oncology nurses towards frailty care: A cross-sectional study based on knowledge-attitude-practice theory in 2024 - Xiaoxue Chen; Fang Xiao; Yuhua Miao; Huiying Qin; Lirong Yang; Fang Shen; Xiuhong Yuan (PLoS ONE, 2025)
Background The demand for frailty care is continuously increasing in hospitalized tumor patients with the aging of the population. Nurses are the primary care providers of hospitalized tumor patients with frailty but research on exploring their behavior and associated factors is limited. This study aims to describe the current situation of frailty care behaviors in oncology nurses and to explore the factors influencing frailty care behaviors. Methods From August 1, 2023, to March 31, 2024, this cross-sectional study was conducted among nurses from oncology-related departments in 5 Secondary A (mid-tier hospitals providing comprehensive care) or above hospitals in South China. Convenience sampling was employed to recruit participants. In China, a "Secondary A hospital is a mid-tier hospital that provides comprehensive medical care and handles more complex cases than primary hospitals but is smaller and less specialized than tertiary hospitals. Data were collected using the standardized frailty-knowledge, attitudes, and practices questionnaire (F-KAP) and general information questionnaire including sociodemographic and work-related details. The sub-scale scores of knowledge, attitude, and practice were calculated by summing up the items within each sub-scale. Student’s independent t-test, one-way ANOVA, Pearson’s correlation coefficient, and two kinds of multiple linear regression models were used for data analysis. Results We included a total of 17 (3.70%) male and 443 (96.30%) female participants in this study. The mean total score of oncology nurses for frailty care behaviors was 33.26±6.61. The three lowest scoring behaviors were “conduct frailty measurements and screening for patients (3.30±1.12)”, “accumulate frailty-related knowledge in daily work (3.59±0.87)”, and “actively pay attention to the patient’s debilitating condition”. Pearson’s correlations analysis showed that nursing grades (r = 0.13), frailty-related training willingness (r = 0.18), nursing frail patients experience (r = 0.22), frailty-related knowledge learning experience (r = 0.33), frailty-related training experience (r = 0.17), frailty care knowledge (r = 0.23), and hospice care attitudes (r = 0.54) were positively associated with frailty care behaviors. Two kinds of multiple linear regression models both showed that the factors most significantly associated with the oncology nurses’ frailty care behaviors are their self-rated subjective knowledge and attitudes towards frailty identification. Conclusion Oncology nurses practiced relatively low-frequency frailty in daily work. Our findings provide theoretical support for improving frailty care attitudes among nurses and enhancing patient quality of life.